2017
DOI: 10.1124/jpet.117.244467
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell–Suppressing Activity of Chrysotoxine, a Bibenzyl fromDendrobium pulchellum

Abstract: Cancer stem cells (CSCs) have been recognized as rare populations driving cancer progression, metastasis, and drug resistance in leading cancers. Attempts have been made toward identifying compounds that specifically target these CSCs. Therefore, investigations of novel therapeutic strategies for CSC targeting are required. The cytotoxic effects of chrysotoxine on human non-small cell lung cancer-derived H460 and H23 cells were evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…Since these five compounds were diluted in dimethyl sulfoxide (DMSO), the same concentration of DMSO was added to the control culture without any compounds. We tested three known therapeutic concentrations [5][6][7][8][9], which were 5, 10 and 20 μM. After 2 hours of incubation, we stimulated monocytes by adding 100 ng/mL LPS and incubated for four more hours.…”
Section: Evaluation Of Immune Modulatory Effects Of Dendrobium Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these five compounds were diluted in dimethyl sulfoxide (DMSO), the same concentration of DMSO was added to the control culture without any compounds. We tested three known therapeutic concentrations [5][6][7][8][9], which were 5, 10 and 20 μM. After 2 hours of incubation, we stimulated monocytes by adding 100 ng/mL LPS and incubated for four more hours.…”
Section: Evaluation Of Immune Modulatory Effects Of Dendrobium Compoundsmentioning
confidence: 99%
“…Some of these metabolites exhibit a wide spectrum of pharmacological activities, including antioxidant, antiinflammatory, antidiabetic, antitumor, antimicrobial and neuroprotective activities [2,4]. For example, purified bibenzyls and phenanthrenes, such as chrysotoxine from D. pulchellum, cypripedin from D. densiflorum, gigantol from D. draconis and moscatilin from D. brymerianum, have been demonstrated to show promising inhibitory effects on human in vitro cell line models of lung cancer growth and metastasis [5][6][7][8][9]. However, whether these therapeutic effects can be also seen in primary human cells and/or in vivo remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhummaphan et al investigated the suppressive effects of chrysotoxine on CSC-rich populations of H460 and H23 cells and primary CSCs in three-dimensional (3D) culture and showed that non-toxic doses (≤20 μM) of chrysotoxine inhibited CSC-like phenotypes and decreased CSC markers CD133, CD44, ABCG2 and ALDH1A1 which were mediated through a Src-AKT-Sox2-dependent mechanism (116).…”
Section: Natural Product Targeting Lung Cancer Stem Cellsmentioning
confidence: 99%
“…The key benefits of natural compounds are the abundance of plants, compound diversity, and cost effectiveness. In focusing on CSCs and tumor growth inhibition, previous studies have reported the promising activities of the bibenzyl derivative chrysotoxine in the suppression of AKT and Src [18]. In vivo studies further revealed that the bibenzyl derivative moscatilin reduced tumor volumes of lung and esophageal cancer xenografts [19,20].…”
Section: Introductionmentioning
confidence: 99%